Phosphoglycerate Mutase 1: Its Glycolytic and Non-Glycolytic Roles in Tumor Malignant Behaviors and Potential Therapeutic Significance - Li, Na (Onco Targets Ther, 2020)
Phosphoglycerate mutase 1 (PGAM1) is an important enzyme that catalyzes the reversible conversion of 3-phosphoglycerate and 2-phosphoglycerate during the process of glycolysis. Increasing evidence suggests that PGAM1 is widely overexpressed in various cancer tissues and plays a significant role in promoting cancer progression and metastasis. Although PGAM1 is a potential target in cancer therapy, the specific mechanisms of action remain unknown. This review introduces the basic structure and functions of PGAM1 and its family members and summarizes recent advances in the role of PGAM1 and various inhibitors of cancer cell proliferation and metastasis from a glycolytic and non-glycolytic perspective. Recent studies have highlighted a correlation between PGAM1 and clinical features and prognosis of cancer as well as the development of target drugs for PGAM1. The integrated information in this review will help better understand the specific roles of PGAM1 in cancer progression. Furthermore, the information highlights the non-glycolytic functions of PGAM1 in tumor metastasis, providing an innovative basis and direction for clinical drug research.